Analisa Keputusan Pembelian Pada PT Subitu Kreasi Busana Cabang Manokwari - Bopeng, Louis S; Redjau, Naomi Merty; Sabarofek, Margareth S (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2021)
The purpose of this research is to (1) Determine the cultural factors that affect purchasing decisions (2) Social factors affect purchasing decisions (3) Personal faktors affect purchasing decisions (4) Psychological factors affect purchasing decisions (5) Cultural, social, personal and psychological factors simultaneously influence the purchasing decisions. used 150 respondents with a sampling technique using non-probability sampling methods and multiple linear regression analysis techniques. The results showed that the purchasing decisions at PT Subitu are more to individual or psychological and personal decisions of consumers. Culture and social do not become indicators in consumers determining whether or not to buy a product at PT. Subitu. For this reason, PT. The Manokwari branch of Kreasi Busana Subitu must maintain its image, outlook, provide quality and good service to customers. Because psychologically, consumers are comfortable and personally fit their wishes. Then the buying decision will be taken by the consumer.